(untitled) (IMC Journal of Medical Science, 2017)
Background and objective Disaster prone coastal population has least accessibility to health care and very little is known about the prevalence of diabetes, diabetic retinopathy (DR) and visual impairment. This study addressed the prevalence of visual impairment and DR and risk factors related to DR among population residing in disaster prone areas of Bangladesh. Methods: Thirty-two coastal communities in six coastal districts were purposively selected. All coastal people of age 18 years or more were considered eligible. Investigations included clinical history, anthropometry (height, weight, waist- and hip-girth), blood pressure and fasting blood glucose (FBG). The participants with hyperglycemia (FBG ?5.6mmol/l) were undertaken for eye examination. Visual acuity was measured bilaterally using the Snellen chart. An Early treatment diabetic retinopathy study (ETDRS) cut out chart with E Optotypes was used. Results: A total of 7567 participants volunteered and 1540 had hyperglycemia (FBG ?5.6mmol/l). Of the hyperglycemic participants, 1214 (91.7%) participated for complete eye examination. Visual impairment of any type was found in 14.1%, any type cataract in 27.8% and any type DR in 18%. The participants of advancing age of higher social class and higher central obesity had excess risk for developing DR. The participants with known family history of diabetes also had greater risk. Compared with the group having FBG 5.6 6.9mmol/l those having FBG >6.9mmol/l had significant risk for DR (OR 3.11, 95%CI 2.04 4.76). Conclusion: The study concludes that visual impairment and cataract of any type is almost comparable with other coastal populations. The coastal people had higher prevalence of DR compared to rural population from other areas of Bangladesh and it was also higher than global estimate. The persons with higher age from higher social class with higher central obesity had excess risk for DR. The risk of DR increased with increasing hyperglycemia. Further study may be undertaken to confirm these findings. IMC J Med Sci 2016; 10(1): 10-17